2013
DOI: 10.1371/journal.pone.0055341
|View full text |Cite
|
Sign up to set email alerts
|

How Does Fiction Reading Influence Empathy? An Experimental Investigation on the Role of Emotional Transportation

Abstract: The current study investigated whether fiction experiences change empathy of the reader. Based on transportation theory, it was predicted that when people read fiction, and they are emotionally transported into the story, they become more empathic. Two experiments showed that empathy was influenced over a period of one week for people who read a fictional story, but only when they were emotionally transported into the story. No transportation led to lower empathy in both studies, while study 1 showed that high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
251
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(311 citation statements)
references
References 51 publications
19
251
1
11
Order By: Relevance
“…This so-called sleeper effect could also apply to other effects than persuasion, like empathy and reflection. In their study on reading and empathy, Bal and Veltkamp (2013) indeed found such a sleeper effect: the effects did not occur right after the reading but one week later. Yet, as said before, Bal and Veltkamp did not systematically compare different genres, so it still remains to be seen under which conditions the sleeper effect occurs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This so-called sleeper effect could also apply to other effects than persuasion, like empathy and reflection. In their study on reading and empathy, Bal and Veltkamp (2013) indeed found such a sleeper effect: the effects did not occur right after the reading but one week later. Yet, as said before, Bal and Veltkamp did not systematically compare different genres, so it still remains to be seen under which conditions the sleeper effect occurs.…”
Section: Discussionmentioning
confidence: 88%
“…Respondents in the literary condition did not show greater changes in self-reported affective empathy. Bal and Veltkamp (2013) did find that reading a fiction text (as opposed to a non-fiction newspaper article) caused an increase in respondents' self-reported affective empathy (measured again by Davis' IRI), but this effect only held for those participants who felt emotionally transported in the story (measured by the narrative engagement scale by Busselle/Bilandzic 2009).…”
Section: Effects: the Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that Theory of Mind (Zunshine, 2006) and narrative empathy (Keen, 2013) are process components of reading literary fiction (e.g., Bal & Veltkamp, 2013;Kidd & Castano, 2013). Zunshine (2006) defined Theory of Mind as 'our ability to explain people's behavior in terms of their thoughts, feelings, beliefs, and desires' (p. 6).…”
Section: Reading Literary Fiction: Changes In Self and Social Perceptmentioning
confidence: 99%
“…One should find mechanisms to incline well-known, recognizable publicists to realize programs devoted to reviewing books and movies, who would like to advocate such cultural products [78,79]. Scientific publications in the field of mental health services should discuss and propose examples of such literary and cinematographic products.…”
Section: Organization Of Changes In Education and Stimulation Of Cultmentioning
confidence: 99%